Mortgage lending experience in agriculture - Jones, Lawrence A.; Durand, David; National Bureau of Economic Research (Princeton, Princeton University Press, 1954)
The main purpose of the project was to determine some of the important causes of farm mortgage distress, The authors gave emphasis on to the two decades between the world wars, when widespread debt difficulties occurred.
"A study by the National Bureau of Economic Research, New York."
Bibliographical footnotes.
osa 25/1/19
Loans
Keywords: Farm mortgages; Agricultural credit